EB Virus and the Treatment of Lymphomas. Issue 5916 (25th May 1974) - Salm, R.
Abstract : The high incidence of EB virus infections (and possibly of other viruses) in patients with African lymphoma and, to a lesser extent, in patients with lymphosarcoma in the temperate zones, is thought to be due to its being a passenger virus which persists in the human body and, since it is lymphotropic, presents an opportunistic infection of proliferating lymphoid cells. The thesis is put forward that by entering the cell nucleus, the virus renders malignant lymphoid cells more vulnerable to cytotoxic drugs. Hence a deliberate policy of EB virus inoculation before starting chemotherapy might achieve a more rapid response and longer remissions in indigenous lymphomas of the temperate zones, and might possibly render drug-resistant cases once more drug-sensitive.